A theoretical study on the electronic structures and equilibrium constants evaluation of Deferasirox iron complexes. (October 2016) - Salehi, Samie; Saljooghi, Amir Shokooh; Izadyar, Mohammad
Graphical abstract: Highlights: The vital role of some iron complexes in biological systems and medicine is irrefutable. A theoretical study was performed to investigate the Deferasirox complexation with iron as a chelator. Electronic structures and equilibrium constants for Fe-DFX complexes in the gas phase, water and DMSO were obtained. Theoretical results showed that Fe-DFX complexes, how to act in biological systems, especially in chelation therapy. Abstract: Elemental iron is essential for cellular growth and homeostasis but it is potentially toxic to the cells and tissues. Excess iron can contribute in tumor initiation and tumor growth. Obviously, in iron overload issues using an iron chelator in order to reduce iron concentration seems to be vital. This study presents the density functional theory calculations of the electronic structure and equilibrium constant for iron-deferasirox (Fe-DFX) complexes in the gas phase, water and DMSO. A comprehensive study was performed to investigate the Deferasirox-iron complexes in chelation therapy. Calculation was performed in CAMB3LYP/6-31G(d, p) to get the optimized structures for iron complexes in high and low spin states. Natural bond orbital and quantum theory of atoms in molecules analyses was carried out with B3LYP/6-311G(d, p) to understand the nature of complex bond character and electronic transition in complexes. Electrostatic potential effects on the complexes were evaluated using the CHelpG calculations. The results indicated that higher affinity for Fe(III) is not strictly a function of bond length but also the degree of Fe–X (X = O, N) covalent bonding. Based on the quantum reactivity parameters which have been investigated here, it is possible reasonable design of the new chelators to improve the chelator abilities.